SandCanvas: New Expressions in Sand Animation - Kazi, Rubaiat Habib (Institutional Knowledge at Singapore Management University, 2011)
Sand animation is a performance art technique in which an artist tells stories by creating animated images with sand. This video demonstrates the creative possibilities of SandCanvas, a new multi-touch digital artistic medium inspired by sand animation that simplifies the creation of sand animations. SandCanvas’s color and texture features enable faster, more dramatic transitions, while its mixed media and gesture recording features make it possible to create entirely new experiences. Session recording and frame capture complement these capabilities by simplifying post-production of sand animation performances.